Development of performance loss functions for healthcare applications. (2017) - Pegues, Kathryn K.
Recent advances in medical knowledge and increased technological capability have combined to make the role of a healthcare provider more challenging. Medical professionals are routinely expected to digest a vast amount of data and develop actionable recommendations. This common 'expectation' of healthcare providers creates an opportunity for increased collaboration across the scientific community in the development of better methodologies for transforming data into information. This paper seeks to establish an informative exchange as to how quality engineering methodologies can be applied to treatment protocol selection. This work describes how to adapt the quality loss function for use within the healthcare domain. Reference interval-based performance functions have application in the development of new metrics for health assessments.